DISPOSISI MATEMATIK TERHADAP KEMAMPUAN BERPIKIR KREATIF MATEMATIK SISWA SMK - Ribka Yohana; Luvy Sylviana Zanthy (Departement of Mathematics Education, 2019)
This study aims to determine the effect of students' mathematical dispositions on mathematical creative thinking skills. The method of this study uses correlational methods and quantitative approaches. The population in this study were students of one of the Vocational Schools in West Bandung Regency and the sample of this study was 31 students of the XI TEI class. The instrument in this study was a test of mathematical creative thinking skills as much as 4 items of the description questions, then the non-test instruments were in the form of mathematical dispositions of 20 scales of positive and negative statements. The stage carried out in this study was the filling of mathematical disposition questionnaires, tests of mathematical creative thinking skills. The results of this study concluded that mathematical dispositions have a positive effect on students' mathematical creative thinking abilities of 1.7% and 98.3% are influenced by other factors beyond mathematical disposition